1989
DOI: 10.1021/tx00007a006
|View full text |Cite
|
Sign up to set email alerts
|

Enantiotopic differentiation during the biotransformation of valproic acid to the hepatotoxic olefin 2-n-propyl-4-pentenoic acid

Abstract: The enantiomers of 2-[( 3-13C]-n-propyl)pentanoic acid [(R)- and (S)-[13C]VPA] were employed as metabolic probes to investigate stereochemical aspects of the biotransformation of valproic acid (VPA) to 2-n-propyl-4-pentenoic acid (delta 4-VPA), a hepatotoxic metabolite of VPA. When incubated with hepatocytes freshly isolated from untreated male rats, each labeled substrate (initial concentration 1.0 mM) underwent metabolism to [13C]-delta 4-VPA, the formation of which was time-dependent and occurred at a rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…This reaction was investigated in detail for the desaturation of valproic acid to 2-propyl-4-pentenoic acid. [137][138][139][140][141] The introduction of a double bond into the valproic acid hydrocarbon terminus is readily rationalized by two mechanisms (Figure 16). Both of these mechanisms are initiated by hydrogen abstraction from the ω-1 carbon of valproic acid.…”
Section: Probes For Cationic Intermediatesmentioning
confidence: 99%
See 1 more Smart Citation
“…This reaction was investigated in detail for the desaturation of valproic acid to 2-propyl-4-pentenoic acid. [137][138][139][140][141] The introduction of a double bond into the valproic acid hydrocarbon terminus is readily rationalized by two mechanisms (Figure 16). Both of these mechanisms are initiated by hydrogen abstraction from the ω-1 carbon of valproic acid.…”
Section: Probes For Cationic Intermediatesmentioning
confidence: 99%
“…However, the evidence for a cation provided by this desaturation process is tainted by the fact that a mechanism can be formulated that only requires a radical intermediate. This reaction was investigated in detail for the desaturation of valproic acid to 2-propyl-4-pentenoic acid. The introduction of a double bond into the valproic acid hydrocarbon terminus is readily rationalized by two mechanisms (Figure ). Both of these mechanisms are initiated by hydrogen abstraction from the ω-1 carbon of valproic acid.…”
Section: Oxygen Insertion Into the C−h Bondmentioning
confidence: 99%
“…Desaturation has been experimentally observed for a number of P450 substrates including valproic acid, [54][55][56][57][58] ezlopitant, 59 sterols such as testosterone, 60 and long chain fatty acids, including lauric acid. 61 While two possible mechanisms may be devised for Cpd I-catalyzed desaturation, proceeding through either radical or carbocation intermediates, prior theoretical studies of trans-2-phenyl-iso-propylcyclopropane oxidation have suggested that a carbocation intermediate should dominate.…”
Section: Substrate Desaturationmentioning
confidence: 99%
“…Phenobarbital induces the formation of 4-en-VPA from VPA via the microsomal cytochrome P-450 system (25)(26)(27). Chronic cotreatment of young rats with VPA and phenobarbital doubled the plasma 4-en-VPA level and induced hepatic steatosis (7, 8).…”
mentioning
confidence: 99%